If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(9n + 3) = 7n + -3 Reorder the terms: 9(3 + 9n) = 7n + -3 (3 * 9 + 9n * 9) = 7n + -3 (27 + 81n) = 7n + -3 Reorder the terms: 27 + 81n = -3 + 7n Solving 27 + 81n = -3 + 7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7n' to each side of the equation. 27 + 81n + -7n = -3 + 7n + -7n Combine like terms: 81n + -7n = 74n 27 + 74n = -3 + 7n + -7n Combine like terms: 7n + -7n = 0 27 + 74n = -3 + 0 27 + 74n = -3 Add '-27' to each side of the equation. 27 + -27 + 74n = -3 + -27 Combine like terms: 27 + -27 = 0 0 + 74n = -3 + -27 74n = -3 + -27 Combine like terms: -3 + -27 = -30 74n = -30 Divide each side by '74'. n = -0.4054054054 Simplifying n = -0.4054054054
| 10(8x-11)=370 | | 3x+(2x-10)=190 | | 8(4n-2n)+n+1+2n-3= | | 5(6x+13)=245 | | 11y=45 | | 8+6m+m-2= | | 3-7x^2+9x= | | .6w+.2=-3+w | | 7(5x+11)=287 | | x^2+7x-136=0 | | -18n+12=-14n-12 | | 8x^2+13x-3=-8 | | 5r+6+8r+3= | | 6(3x-1)-2x=2(2x-51-8) | | 6(9x-2)=366 | | ln*(3x)=6.4 | | ln*3x=6.4 | | 3a+a=24 | | Log(2x+5)=1 | | 10+8v+v+1= | | 9m-m+3(m+2)=4m+7 | | tgx=4 | | 9x-8=71 | | 11x-(3x+10)=4x+2 | | 3x+14=143 | | 0.40(m-3)=2+.375m | | x^2+7x+1=9 | | 4x-8=6x-24 | | 3(3+4y)+8=245 | | 4x-12-8=0 | | 5(8x-14)=170 | | 2(6)-7= |